New Business Valuation Methodology (MVNE) - Maquieira V., Carlos; Willatt H., Christian (Estudios de Administración, 2006)
This paper presents a new methodology called MVNE to valuation of new ventures based on APV (Adjusted Present Value) principles. Company valuation of established firms is a very well studied and documented topic. In opposite, valuation of early stage companies is a much less known case and it presents challenges in modeling and computing the business value since they usually have operational losses during the first years and later they present a rapid growth. The proposed methodology consists of three basic steps and outlines common mistakes seen in practice. Further, it presents a general solution to compute the present value of interest tax shield related to business value and this solution works whether the firm has profits or losses when debt financing is included. Finally, the methodology allows computing equity value to negotiate ownership when risk capital financing is incorporated.